MUSIK OGLOR DALAM RITUAL SUNATAN DI DESA WONOKARTO KECAMATAN NGADIROJO KABUPATEN PACITAN - Zhenley Octa Sinaga (SELONDING, 2018)
Oglor is one of the traditional arts that developed in the village community Wonokarto, in this case Oglor music is used as a means of circumcision ritual in the village Wonokarto. Where the owner of the intent more believes with chanting poem played Oglor music will be faster delivered to God. The form of music presentation Oglor in the ceremony sunatan as a means of accompaniment, bringing many songs and Islamic poems taken from the book barzanji. Oglor music has always been used as a medium of prayer in the great days of religion and especially for traditional ceremonies in the village of Wonokarto. The call of poetry containing prayers with the accompaniment of kendang, centrifugal and flying instruments into an inseparable unity. Thus it can be concluded that Oglor as a means of ritual circumcision ceremony in Wonokarto village is one of the tradition of Wonokarto villagers, where the owner chooses to bring Oglor music in every ritual ceremony of sunatan ceremony. Because every verse of the song that is sung has meaning for the good of the child in the future and is celebrated as gratitude to God Almighty.